Kaiguo dadian - Zhao Yu,
'Ceremony proclaiming the founding of the State.' Printno. 7-5305.21807. Place of persons f.l.t.r.: Lin Boqu, Zhou Enlai, Dong Biwu, Zhu De, Liu Shaoqi, ?, Song Qingling, Guo Moruo, Li Jishen, Zhang Lan, Gao Gang, Mao Tse-Tung. See also BG E13/105.